2021
DOI: 10.1097/mpa.0000000000001731
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Eosinophils and the Eosinophil-to-Lymphocyte Ratio on Survival Outcomes in Stage II Resectable Pancreatic Cancer

Abstract: Objectives The relationship between eosinophils and cancer prognosis is unknown. Therefore, we analyzed the relationship between circulating eosinophils and the survival of stage IIA and IIB pancreatic cancer patients who underwent surgical resection. Methods This study included a retrospective cohort of 67 consecutive patients. Patients were categorized into two different groups based on the optimal cutoff for pretreatment levels of each biomarker, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…With respect to ELR, Ohkuma R, et a. [24] found that low ELR was an independent prognostic factor of clinical outcome in stage II resectable pancreatic cancer. [24] In AECOPD, ELR was a potential indictor of eosinophilic airway in ammation [25].…”
mentioning
confidence: 98%
“…With respect to ELR, Ohkuma R, et a. [24] found that low ELR was an independent prognostic factor of clinical outcome in stage II resectable pancreatic cancer. [24] In AECOPD, ELR was a potential indictor of eosinophilic airway in ammation [25].…”
mentioning
confidence: 98%
“…Previous studies demonstrated that high levels of tumor-infiltrating eosinophils are positively associated with better prognosis, inversely correlated with stage and related to decreased risk of death caused by cancer progression [ 32 , 33 ]. Furthermore, a low number of eosinophils is related with short overall survival and seems to be an independent prognostic factors for poor outcomes in patients with pancreatic cancer [ 34 ]. Eosinophils are a major component of the type II immune response and are capable of secreting many factors such as cytotoxic granules, lipids, growth factors, cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ELR has been considered as a systemic inflammatory indicator. Prior studies reported that there was a significant relationship between ELR and adverse events in patients with malignancy [6,7]. Moreover, Yılmaz et al recently found that subjects with angiographic isolated CAE had significantly greater ELR values [8].…”
Section: ) or -Odds Ratio CI -Confidence Interval Ht -Hypertension Hd...mentioning
confidence: 97%
“…The eosinophil-to-lymphocyte ratio (ELR) is a new inflammatory bioindex that takes into account both eosinophil and lymphocyte levels [6]. In recent studies, the relationship between the ELR and adverse events in patients with malignancy has been demonstrated [6,7]. Besides that, the predictive value of this index has been investigated for isolated coronary artery ectasia presence and severity [8].…”
Section: Introductionmentioning
confidence: 99%